DEHYDRIN- STRESS PROTEINS OF BIRCH BUDS IN CONTRASTING CLIMATIC REGIONS - Tatarinova, T D; Budyakina, V V; Vetchinnikova, L V; Perk, A A; Ponomarev, A G; Vasilieva, I V (T͡S︡itologii͡a, 2017)
Stress proteins dehydrins have been identified using specific antibodies in buds silver birch (Betula pendula Roth) growing in contrasting climatic conditions of the regions Karelia and Central Yakutia. Dehydrins in buds of plants are presented in two areas: medium molecular weight (56-73 kDa) and low molecular weight (14-21 kDa), and 17 kDa dehydrin was detected in all studied birches. 14-21 kDa dehydrins are the most susceptible to seasonal changes. Regardless of birch growing region, dehydrines 14-21 kDa show significant increase in their level in the autumn and winter when the trees are characterized by the highest frost resistances. Dehydrins have relealed intraspecific polymorphism, more pronounced in Yakutia plants in conditions of extreme continental climate, compared with Karelia, which is probably due to the peculiarities of woody plants to adapt to the extremely low winter temperature of the permafrost zone.